Ways of restoration of the degraded pasturable lands of the territory of the southern Kazakhstan (Eurasian Journal of Ecology, 2016)
The article deals with the conditions of contemprorary pastures and the ways of their improving. The article also commeces on the problem of creating stock-breeding complexes with the help of innovative technologies. To restore degraded pastures are recommended to use the forage plant species tolerant to local climatic conditions, sustainable grazing, high yield, creating mixed pasture forage grasses, seeding rate ofpasture forage plants and ways to use the pasture for the restoration of degraded lands.
Keywords: the degraded pastures; an agrotechnology; arid areas; culture; an introduction; seeds